2011
DOI: 10.1017/s0022215111000880
|View full text |Cite
|
Sign up to set email alerts
|

Audit of handover in an ENT unit

Abstract: We demonstrated a substantial improvement in the quality and completeness of written handover, comparing the second and first audit periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…). Studies found in the literature where clinical handover had undergone an evaluation method ranged from questionnaires (which are reliant on the respondent providing open and honest response regarding their own practice) to action research studies where observational behaviour was viewed then critiqued, this is open to the observer's interpretation of the event (Bomba & Prakash , Ellul & Robson , Johnson et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…). Studies found in the literature where clinical handover had undergone an evaluation method ranged from questionnaires (which are reliant on the respondent providing open and honest response regarding their own practice) to action research studies where observational behaviour was viewed then critiqued, this is open to the observer's interpretation of the event (Bomba & Prakash , Ellul & Robson , Johnson et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies19 21 26 27 31 32 39 41 44 46 gave no information on the number of handovers they included (see online supplementary table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies gave no information on any component of their study design timeline34–37 41–43 and 14 gave no information on one or more study timeline components 19 21–23 25 29–32 39 40 45–47…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations